Pedophilic Sexual Interests Screening Scale (SSPI-2) - Rodríguez Padilla, Alexa Liliana; Pérez García, Paula Sofía; Ortiz González, Liliana; Arévalo Acuña, Maria Camila (Pensando Psicología, 2025)
Research indicates that approximately 50% of men convicted of sexual offenses against minors may meet the diagnostic criteria for pedophilia. However, the available instruments for evaluating such interests are limited and complex to administer, as is the case with plethysmography. The Screening Scale for Pedophilic Interests (SSPI-2) is a screening tool designed to detect pedophilic sexual interests and consists of six items in its second version. For its use in the Colombian context, and with prior authorization by one of its authors, Dr. Michael Seto, the scale was translated into Spanish and back-translated into English by bilingual psychology professionals. Minor language adjustments were made by experts in sexuality and offender assessment in prison settings, in order to improve semantic clarity without altering the content. For the pilot study, a sample of 71 judicial case files of men convicted of sexual offenses was used, and the SSPI-2 items were applied to analyze the cases. The results support the potential utility of the scale in assessing pedophilic sexual interests, as well as its use as a screening tool within the Colombian prison context. Differences were observed between participants with pedophilic sexual interests and those without. This study is part of the broader project Adaptation of the SSPI-2 Scale, led by Universidad El Bosque, within its research line in Criminological Psychology. The adaptation and implementation of tools like the SSPI-2 not only contribute to diagnostic assessment with reliable and valid instruments in penitentiary contexts for individuals deprived of liberty for sexual offenses, but also strengthen intervention and treatment strategies aimed at improving voluntary control over problematic sexual behaviors and reducing recidivism.